Soil amendments with farm yard manure and poultry manure confer tolerance to salt stress in rice (Oryza sativa L.) (Research in Agriculture Livestock and Fisheries, 2016)
Salinity causes unfavorable environment that restricts normal crop production. Organic amendments could contribute to the improvement of crop production in coastal areas. Two rice varieties viz. BRRI dhan29 (salt-sensitive) and Binadhan-8 (salt-tolerant) were grown in replicated pots to investigate the mitigation potential of salt stress in rice by organic amendments. Two doses of farm yard manure (FYM: 5 and 10 t ha-1) and poultry manure (PM: 4 and 8 t ha-1) were mixed with soils before transplanting. Rice plants were exposed to different concentrations of NaCl (25 and 50 mM) at active tillering stage. Salt stress caused a significant reduction in growth and yield of both rice varieties. Salt stress also decreased reproductive growth, chlorophyll contents, K+/Na+ ratio, nutrient contents and nutrient uptake in both rice varieties. Salinity caused a significant increase in intracellular proline content in BRRI dhan29 but a decrease in Binadhan-8. Organic amendments with FYM and PM resulted in an increase in growth and yield components, chlorophyll content, K+/Na+ ratio and nitrogen (N) uptake. No plants of BRRI dhan29 survived at 50 mM NaCl stress even after addition of FYM and PM. On the other hand, Binadhan-8 conferred tolerance to 50 mM NaCl stress when soils were amended with organic sources, suggesting that cultivation of Binadhan-8 might be profitable in saline affected areas with organic amendments. The present study suggests that organic amendments with FYM and PM confer tolerance to salinity in rice by increasing chlorophyll content, K+/Na+ ratio and N uptake.Res. Agric., Livest. Fish.3(3): 379-386, December 2016